Low-Cost and Ultra-Precise Synchronization Concept for TDoA Localization of Dairy Cows - Klob, Sebastian; Maul, Thomas; Robert, Joerg (Proceedings of the 2023 13th International Conference on Indoor Positioning and Indoor Navigation, IPIN 2023, 2023)
Implementing modern technologies such as localization in an agricultural environment has received significant interest in recent years. These kinds of systems help farmers to manage their farms more economically. Especially dairy cows often move between the stable and pasture area, so frequent localization is needed in both environments. One faces many challenges when implementing such a system, such as energy supply, limited computing power, and bad radio links. This paper presents a system able to synchronize three receive stations for localizing dairy cows on a field with the help of Time-Difference-Of-Arrival. The focus will be on realizing a cost-effective, energy- and computing-efficient concept that minimizes transferred data and that can be deployed in agricultural environments as well as in other possible indoor and outdoor localization scenarios. To implement such a system, a switching receiver is used that alternates between the reception of a Low Power Wide Area Network signal for localization and a Signal of Opportunity for synchronization. No special hardware is required because the synchronization is realized as a Software Defined Radio system. The impairments caused by this kind of receiver, with a particular focus on synchronization, are analyzed and visualized. Also, the effects of phase noise on the frequency estimation are investigated. It is shown that the theoretical bounds for frequency estimation do not limit the switching receivers' performance. Initial measurements for the proposed architecture are shown.
CRIS-Team Scopus Importer:2024-11-19
Keywords: IoT; Localization; MCRB; Signal of Opportunity; Software Defined Radio; Synchronization